Measurement of the tt̄ production cross-section in pp collisions at √s = 5.02 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; et al. (Journal of high energy physics, 2023)
The inclusive top-quark pair tt̄ production cross-section sigma tt̄ is measured in proton-proton collisions at a centre-of-mass energy √s = 5.02 TeV, using 257 pb^−1 of data collected in 2017 by the ATLAS experiment at the LHC. The tt̄ cross-section is measured in both the dilepton and single-lepton final states of the tt̄ system and then combined ...